(untitled) (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
Question analysis is an activity that is done to identify the deficiencies in the learning outcome test and is intended to identify good questions, bad questions, and the problem of these questions. This analysis gives information on a question problem and how to fix it. The analysis of cognitive degree was a type of question analysis that aims to reveal the mix of guaranteed cognitive degree in questions. The author knows that this analysis was less done. This study aims to identify and describe the mix of cognitive degree guaranteed in the National Final Exam Questions for the Arabic Secondary Language Study. The study method used is descriptive analysis. The subjects of this study were questions on the Arabic National Examination issued by the Educational Assessment Center of the Ministry of Education and Culture of the Republic of Indonesia for the 2013-2014 academic year. This exam is attended by students from the language department of Indonesia’s state high schools. The total questions of this exam is 50. The result of this study is that the percentage of the cognitive degree guaranteed in the National Final Exam Questions for the Arabic Secondary, namely: C1 (52%), C2 (20%), C3 (22%), C4 (6%), C5 (0%) and C6 (0%). This result does not meet the percentage of questions that support the achievement of Basic Competence, namely, 30% for C1 and C2, 40% for C3 and C4, and 30% for C5 and C6